All Days 2013
DOI: 10.2118/165493-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of Casing Connections for Thermal Well Applications

Abstract: Thermal well technologies, such as Cyclic Steam Stimulation (CSS) and Steam Assisted Gravity Drainage (SAGD), are widely used for the exploration of heavy oil and oilsands resources. Casing connections are one of the most critical components in thermal wells in terms of the wellbore structural and pressure integrities. High temperature operation of thermal wells inevitably imposes significant axial loads on the casing connections, and as a result, a plastic strain design concept must be used for the casing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…Murtagian et al [6] observed large influence of thread compound on the evolution of leakage rates in premium connections. Temperature is known to modify seal compound properties, and to induce axial stresses that impact sealability [7][8][9]. Also, it is recognized that nature of contained fluids affects sealing behavior [10,11].…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Murtagian et al [6] observed large influence of thread compound on the evolution of leakage rates in premium connections. Temperature is known to modify seal compound properties, and to induce axial stresses that impact sealability [7][8][9]. Also, it is recognized that nature of contained fluids affects sealing behavior [10,11].…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Some assumptions have been made for simplified models, such as ignoring the screw angle, assuming the load on the joints and so on. The influence of temperature effect on the performance of premium connections is seldom analyzed in accordance with the test steps of ISO 13679 (Tao et al , 2013; Zhang et al , 2016; Li et al , 2017). In order to truly reflect the integrity of premium connections in service environment, a three-dimensional finite element model of a premium connection commonly used in complex wells is established in ABAQUS finite element analysis software.…”
Section: Introductionmentioning
confidence: 99%
“…Análises de temperatura e flexão são pouco exploradas, mas pesquisadores ressaltam a necessidade de pesquisa neste campo. A temperatura aumenta proporcionalmente com a profundidade e induz ciclos de expansão e retração no aço, introduzindo esforços axiais de compressão que ocasionam plastificação da conexão (TAO; XIE, 2013;TAO, 2010). CHEN et al (2018) analisam a influência da flexão nas pressões de contato na rosca e ombro de contato de conexões proprietárias.…”
Section: Metodologiaunclassified
“…Em especial, a flexão reduz o selo de conexões proprietárias pela redução das pressões e área de contato no ombro (de contato). Solicitações de flexão têm sido avaliadas sobre modelos axissimétricos, através do uso de elementos finitos axissimétricos implementados com formulações especiais (CHANG, 2008;XIE, 2013). BAHAI (2001) utiliza submodelos axissimétricos para avaliar os efeitos da flexão na concentração de tensões nos vales dos filetes.…”
Section: Metodologiaunclassified
See 1 more Smart Citation